The Effectiveness of E-Module in Improving Critical Thinking Skills of High School Students in Learning Physics - Arimbi Rachmayani; Jumadi; Supahar (Jurnal Penelitian Pendidikan IPA, 2023)
This paper was written to explain the influence or effectiveness of digital modules or physics e-modules in their contribution to improving the critical thinking skills of high school students or their equivalent. The descriptive qualitative study method is used to achieve the purpose of this paper. By using highly reputable international and national journals as references in the preparation of this paper. During this pandemic educator are required to design learning concepts and tools that can improve critical thinking skills, because critical thinking is a basic ability that must be possessed in the 21st century. From this paper it results that the use of e-modules in physics learning is very effective in improving students' critical thinking skills teach with various approaches.